Evaluation of the Impact Resistance of Various Composite Sandwich Beams by Vibration Tests - Amir Shahdin; Joseph Morlier; Laurent Mezeix; Christophe Bouvet; Yves Gourinat (Shock and Vibration)
Impact resistance of different types of composite sandwich beams is evaluated by studying vibration response changes (natural frequency and damping ratio). This experimental works will help aerospace structural engineer in assess structural integrity using classification of impact resistance of various composite sandwich beams (entangled carbon and glass fibers, honeycomb and foam cores). Low velocity impacts are done below the barely visible impact damage (BVID) limit in order to detect damage by vibration testing that is hardly visible on the surface. Experimental tests are done using both burst random and sine dwell testing in order to have a better confidence level on the extracted modal parameters. Results show that the entangled sandwich beams have a better resistance against impact as compared to classical core materials.